2005
DOI: 10.1140/epjb/e2005-00351-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectral cut-off in the efficiency of the resistive state formation caused by absorption of a single-photon in current-carrying superconducting nano-strips

Abstract: We have studied supercurrent-assisted formation of the resistive state in nano-structured Nb and NbN superconducting films after absorption of a single photon. In amorphous narrow NbN strips the probability of the resistive state formation has a pronounced spectral cut-off. The corresponding threshold photon energy decreases with the bias current. Analysis of the experimental data in the framework of the generalized hot-spot model suggests that the quantum yield for near-infrared photons increases faster than … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
156
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(169 citation statements)
references
References 20 publications
(23 reference statements)
7
156
2
2
Order By: Relevance
“…The energy dissipated by the vortex crossing the nanowire leads to a transition to the normal state [20][21][22]. Contrary to early models [23], we found that the detection event cannot be described by the local increase of current density over the critical value due to a photo-generated normal core hotspot.…”
contrasting
confidence: 80%
“…The energy dissipated by the vortex crossing the nanowire leads to a transition to the normal state [20][21][22]. Contrary to early models [23], we found that the detection event cannot be described by the local increase of current density over the critical value due to a photo-generated normal core hotspot.…”
contrasting
confidence: 80%
“…The absorption of one or more photons in a superconducting nanowire drives part of the nanowire to the normal state with a resistance of the order of several kilohms [8][9][10] , which can be detected by using an appropriate readout circuit 7 . SNSPDs have outperformed other near-infrared single photon detector technologies in terms of dark count rate, timing resolution and reset time 1 .…”
Section: Lettermentioning
confidence: 99%
“…For short wavelengths, QE is practically independent on the current or the wavelength and amounts at 1.8% for visible light. We attribute the response in this regime to the photon-induced local non-equilibrium spot, which is further driven into the normal state by the current [5] and, consequently, forms a normal domain. The transition into the normal state occurs because the reduced number of superconducting electrons in the spot cannot carry the applied current.…”
Section: Detector Technology and Experimental Detailsmentioning
confidence: 99%
“…Since the amplitude of the transient voltage is almost entirely controlled by the magnitude of the current, the detector cannot distinguish the number of simultaneously received photons. It has been predicted, that the hot-spot detection scenario has a cut-off in the single-photon detection capability [3] and an indication of this has been found recently [5]. However, due to the change of the detection mechanism for low-energy photons, SNSPD shows lower quantum efliciency *Corresponding author.…”
mentioning
confidence: 98%